HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR MATA PELAJARAN BOGA DASAR KELAS X JASA BOGA DI SMK NEGERI 1 PAINAN - Sari, Ika Purnama; Silfeni, Silfeni; Gusnita, Wiwik (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study aims to 1) describe the motivation of students on subjects Boga Basic Class X Hospitality at SMK Negeri 1 Painan, 2) Describe the student learning outcomes in subjects Boga Basic Class X Hospitality at SMK Negeri 1 Painan, 3) To reveal relationship between motivation and learning outcomes in subjects Basic Culinary Hospitality in class X SMK Negeri 1 Painan. Sample in the study included 30 people with purposive sampling technique. Result of research that student motivation is 76.73% in medium category. Product Moment Correlation test research there is a relationship between motivation and learning outcomes r value of 0.782 and 0.000 sig. The research obtained show that the value of sig 0.000 <0.05 alpha so his decision is Ho refused and Ha is received it can be concluded that there is a strong positive relation between motivation and significant to the learning outcomes on the subjects of class X Basic Culinary Hospitality at SMK Negeri 1 Painan.Keywords: Motivation, Learning Outcomes, Student / i catering services